Charisms and Charismatic Renewal: A Biblical and Theological Study - Mullooparampil, Sebastian (Asian Horizons, 2011)
Francis A. Sullivan, S.J., Charisms and Charismatic Renewal: A Biblical and Theological Study, Bangalore: Theological Publications in India, 2011). Pages: 184. ISBN: 978-81-88821-73-0